Mammary Cystadenoma: Diagnosis and Treatment in a Bitch - Corrêa de Almeida, Gabriela; Ibrahim Isa Abdel Hadi, Najla; Moutinho, Izabelle; Cardoso de Oliveira, Vinícius; Mendes de Oliveira, Victor; Ferreira Gonçalves, Gentil; Elias, Fabiana; Dalmolin, Fabíola (Acta Scientiae Veterinariae, 2024)
Background: Although malignant mammary alteration is highly studied in canine, data about benign lesions is sparse. A study reported 27.1% of benign alteration, being 5.9% cystadenomas. It is a unique or multiple lesion, characterized by lined and well differentiated epithelial cells. The alteration is well recognized in women, opposite to canines, which present cysts or not, and it is more frequent in ovary, kidney, salivary gland, thyroid, pancreas and mammary gland. Related to cysts, ultrasonography and cytological exams help the diagnosis and treatment. In this way, this report presents the diagnosis, the treatment and 4 years follow up canine mammary cystadenoma. Case: A 5-year-old non-spayed Mongrel bitch, weighing 5.9 kg, presented mammary enlargement identified by the owner since 8 months before. The patient had received exogenous contraceptives 3 times, being the last one 12 months before; after detection, the enlargement increased in volume along the time. It was a 9x2x1 cm nodular and fluctuant enlargement in the left inguinal mammary gland; the ultrasound exam confirmed many fluid collection delimited by a thin echogenic capsule and anechoic content. No alterations were detected at other glands and abdomen. Fine-needle aspiration promoted the liquid drainage, which presented no cells identified by cytology for 2 times. The patient was submitted to OVH and nodulectomy and discharged after anesthetic recovery, with prescription of meloxicam, dipyrone and topic chlorhexidine digluconate 1%. After 4 days the owner verified the color change of the skin at the nodulectomy site. We identified a purplish alteration 13 days after, as well as wound healing, being sutures removed and warm compresses prescribed; normal color was verified after 8 days. Posteriorly at 1 and 4 years the patient was evaluated and no clinical, mammary and ultrasonography alterations were detected. Discussion: The non-spayed bitches which receive exogenous contraceptive are more likely to mammary alteration development, as observed in this patient. According to the Brazilian Mammary Consensus, the malignant mammary alteration bigger than 3 cm must be treated by unilateral mastectomy and lymphadenectomy, an aggressive surgery which involves long anesthesia and hemodynamic disturbances due to the surgical stress response. Considering the absence of malignant signs, an encapsulated alteration, the absence of malignant signs and a relatively young patient, the patient was treated by nodulectomy, opposite to the recommended. The benign mammary neoplasms are more susceptible to hormonal influence compared to the malignant one after synthetic progesterone application, since the benign have more progesterone and estrogen receptors. In this way, the OVH was performed in order to reduce the hormonal influence. The OVH was performed firstly to avoid abdominal contamination by liquid or cells, according to the aseptic and atraumatic surgical principles. The histological tumor exam revealed cystadenoma with papillary formation, and mild uterine cystic endometrial hyperplasia not visible by ultrasonography image. Although it was a benign alteration, the authors considered the risk of malignant lesion after exogenous contraceptive. For this, the patient was assessed by clinical and ultrasonography exam 1 and 4 years after to verify recurrence or new lesions, which were not observed and indicated treatment effectiveness. It was recognized that surgical aggressiveness changes the immune response and it predisposes to neoplasm development. Although the authors believe in the positive effect of less aggressive surgery to patients with benign alterations, more studies are necessary to verify the benign neoplasm behavior in order to suggest the adequate treatment. Keywords: benign neoplasm, canine contraceptive, mammary cyst, mastectomy, surgical stress, mammary nodulectomy.